2013
DOI: 10.1038/ctg.2013.1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Vitamin D Supplementation in a Pilot Study of Crohn's Patients

Abstract: OBJECTIVES:Low vitamin D status may be associated with Crohn's disease. A pilot study was performed in patients with mild-to-moderate Crohn's disease to determine the dose of vitamin D needed to raise serum vitamin D levels above 40 ng/ml.METHODS:Patients were evaluated for severity of symptoms using the Crohn's disease activity index (CDAI) and patients with mild-to-moderate (150–400 CDAI scores) Crohn's disease were entered into the study (n=18). Vitamin D3 oral therapy was initiated at 1,000 IU/d and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 24 publications
(27 reference statements)
3
144
1
2
Order By: Relevance
“…A secondary analysis investigating differences in these parameters and based on serum 25(OH)D concentration achieved, was also performed, as newer data suggests that a higher 25(OH)D level may be important for changes in disease activity or inflammation. 1,39 First, we observed that 2000 IU vitD/day taken for 3 mos. was sufficient to raise the 25(OH)D concentrations to 75 nmol/L in 8/12 participants of the treated group, in winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A secondary analysis investigating differences in these parameters and based on serum 25(OH)D concentration achieved, was also performed, as newer data suggests that a higher 25(OH)D level may be important for changes in disease activity or inflammation. 1,39 First, we observed that 2000 IU vitD/day taken for 3 mos. was sufficient to raise the 25(OH)D concentrations to 75 nmol/L in 8/12 participants of the treated group, in winter.…”
Section: Discussionmentioning
confidence: 99%
“…31 In this study, we observed no significant changes in markers of disease activity, namely CDAI, CRP, FC or QoL, in response to vitD; however, when analysed according to the level of 25(OH)D achieved at 3 mos., we found significantly lower CRP, correspondingly higher self-reported QoL and a non-significant reduction in CDAI (p ¼ 0.082). Yang et al 39 conducted a study that aimed to achieve a circulating concentration of 100 nmol/L in CD patients with mild-to-moderate disease. The authors report a significant reduction in CDAI (p < 0.0001) and significant improvement in QoL scores (p < 0.0004) after 24 weeks of supplementation, suggesting that the levels attained may be important to induce changes in disease activity and correspondingly, in QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were treated with either active vitamin D or 25 μg (1000 IU) D 3 daily for 12 months; the authors reported a significant short-term reduction (42) 2013 Australia 40 X (HBI) X √ inverse Jorgensen et al (78) 2013 Denmark 182 √ inverse (CDAI) X -Kelly et al (66) 2011 Ireland 75 X (CDAI) X -Ulitsky et al (79) 2011 USA 403 √ inverse (HBI) --(total n∼785) Other disease outcomes Ananthakrishnan et al (44) 2013 USA 1769 Low 25(OH)D and higher risk of surgery and hospitalisation Zator et al (45) 2013 USA in disease activity (CDAI and CRP) with a more pronounced effect noted for the active form of vitamin D (46) . More recently, Yang et al (47) applied a protocol designed to focus on achieving circulating 25(OH)D levels of 100 nmol/l rather than on administrating a predefined fixed daily dose of vitamin D. In this small study (n 18), patients with mild to moderately active CD were supplemented with oral vitamin D 3 ; this dose was initiated at 25 μg (1000 IU) daily and escalated up to a maximum of 125 μg (5000 IU), to achieve the target circulating 25(OH)D of 100 nmol/l. The key finding was a significant reduction in CDAI scores at 6 months.…”
Section: Vitamin D Status and Associations With Disease Severity In Cmentioning
confidence: 98%
“…Preliminary findings from our pilot intervention study showed that 50 μg (2000 IU)/d vitamin D raised levels from 69 to 92 nmol/l at 3 months, which was accompanied by a modest reduction in CRP but only in participants who achieved serum 25(OH)D >75 nmol/l (50) . Yang et al (47) specifically designed their study to achieve a target circulating 25(OH)D of 100 nmol/l, and achieving this target level was associated with short-term improvements in disease activity.…”
Section: Vitamin D Status and Associations With Disease Severity In Cmentioning
confidence: 99%
“…The primary aim of the present study was to examine the effects on bone metabolism and not disease activity; moreover, the paper did not report the 25(OH)D levels obtained by the groups, which may have not been in the therapeutic range at 12 months. Yang et al (26) titrated vitamin D 3 intake until such a point serum levels were ≥100 nmol/l (commonly requiring 125μg (5000 IU)/d) and reported significant improvements in CDAI with a mean reduction in CDAI from 230 (SD 74) to 118 (SD 66; P < 0·0001). This may suggest a minimum level of 100 nmol/l is required to exert a significant effect on disease severity but further research is warranted.…”
Section: Clinical Studies; Association Between 25-hyroxyvitamin D Levmentioning
confidence: 99%